Negotiating intercultural experience through English as a foreign language in South Korea. (2nd January 2019) - Peck, Catherine; Yates, Lynda
ABSTRACT: The 'intercultural turn' in foreign language education has brought to the fore the need to foster intercultural competences. Yet in contexts where virtually all intercultural communication is mediated by English as a foreign language (hereafter EFL), proficiency in that language determines to a large extent access to intercultural experiences, including coveted opportunities for international work and study. Such high stakes mean that acquiring competence in the language can be an emotionally charged process, and using it an emotionally salient feature of intercultural encounters. This paper draws upon an interview-based study of South Koreans' ideologies of the intercultural to explore the complex emotions associated with using EFL in intercultural experiences. La 'svolta interculturale' nell'insegnamento delle lingue straniere ha messo in evidenza la necessità di promuovere le competenze interculturalie, nel processo, ha minimizzato il processo emotivo di acquisizione delle competenze in una lingua straniera. Tuttavia, in contesti in cui praticamente tutte le comunicazioni interculturali sono mediate dall'inglese, la capacità di parlare la lingua determina l'accesso a opportunità prestigiose per il lavoro e lo studio in contesti internazionali. Questo articolo è basato su una serie di interviste con dei soggetti sudcoreani dove si esplora come loro utilizzano delle complesse emozioni e ideologie interculturali associate all'uso dell'inglese come lingua straniera, per costruire l'esperienza interculturale.